Aplikasi Teori Psikoanalisa Dalam Tugas Belajar - Evita Yulianti Wahidah; Ineu, Ineu Kurniati; Nur Mashani Mustafidah; Zubaidi Wahyono; Asep Kusnadi (Education Reserach Center, 2025)
Sigmund Freud's psychoanalytic theory explains that an individual's behavior, including in the learning process, is influenced by the interaction between the id, ego, and superego. Conflicts between instinctual drives and social norms in the context of learning tasks often lead to anxiety, stress, and procrastination. This study aims to explore how these psychoanalytic dynamics affect students' learning processes. The research method involves qualitative analysis of case studies and interviews with students in educational settings. The findings reveal that the ego plays a crucial role in managing emotional pressures, enabling students to overcome learning barriers more adaptively. In conclusion, applying psychoanalytic theory in education provides a deeper understanding of the psychological barriers students face, leading to a more holistic approach to learning that integrates both cognitive and emotional aspects. Keywords: psychoanalysis, id-ego-superego, academic tasks, defense mechanisms, educational psychology